(untitled) (Global Conference on Medical and Health Sciences, 2026)
This literature review provides a comprehensive analysis of the importance of hygiene in the prevention of dermatological diseases based on scientifically validated sources. Current epidemiological data indicate that skin diseases are highly prevalent worldwide, with a substantial proportion associated with inadequate hygiene practices. The findings demonstrate that adherence to hygienic measures—such as hand hygiene, proper skin care, sanitation, and environmental control—significantly reduces the incidence of dermatological conditions. However, excessive or improper hygiene practices may disrupt the epidermal barrier and contribute to the development of inflammatory skin diseases. The analysis confirms that hygiene is a key and multifactorial determinant in the prevention of dermatological diseases and highlights the need for individualized and comprehensive hygienic strategies to improve population health outcomes.